"Dance of the eagle” – spiritual and artistic heritage of Tuvan people - Sanchay, Choygan H. (The New Research of Tuva, 2014)
Article paints the elements of the "Dance of the eagle” – ritual dance of Khuresh wrestlers, estimates its role in traditional feasts of Tuvans.